Comparing the Assessment Quality of Trained Versus Untrained Peer Examiners in Obstetrics and Gynaecology in OSCE - Beenish Riaz, Huma Afridi, Wajiha Shadab, Itaat Ullah Khan Afridi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Assessment has been shown in studies to have a significant impact on the learning process. There has been a lot of interest in making assessment an important element of the learning process for students. Senior medical students may be able to assist teachers with peer evaluations. There is little evidence to support the idea that peer examiners should be officially trained before taking on the job. Aim: To find the difference in teaching faculty scores of untrained and trained peer examiners in Obstetrics & Gynecology OSCE. Study design: Cross-sectional (analytical) study Place and duration: The study was conducted at Sialkot Medical College Sialkot” affiliated with Imran Idrees Teaching Hospital in Obstetrics /Gynecology department over the period of 6 months from January 2022 to June 2022 Methodology: One hundred and five medical student of 4th year were enrolled for practice of OSCE examination. Forty final year medical students took part in the assessment program as peer examiners. One group of examiners were given 2-hour training session describing about the assigned OSCE stations, marking method, evaluation, and feedback methods. Other group was given only checklist to read with no prior training. Using the checklist and a global rating, senior faculty and peer student examiners (both trained and untrained groups) simultaneously assessed students in basic Obstetrics /Gynecology clinical skills at 4 OSCE stations. Every station ran for five minutes (3 minutes of evaluation while 2 minutes of feedback). A comparison between the check list and global rating scores of trained and untrained peer student examiners was made. SPSS version 21 was used to calculate intra-rater reliability was assessed to build the consensus of faculty examiners with the trained and untrained peer examiners according to checklist scores and global rating. Results: Student examiners found sitting at OSCE stations as a useful learning experience. Observing different performances at OSCE stations was so absorbing and it gave them awareness about examination procedure. Practical implication. Peer assessors in a formative OSCE could be successfully implemented in the curriculum of a large medical school with more than 100 students annually. They can be trained to conduct undergraduate assessments of their junior peers and can prove to be very reliable and effective assessors. Conclusion: Peer markers who underwent the formal training session showed the capacity to assess fourth-year students with suitable consistency and devotion. Hence training helped to improve peer marker consensus with faculty. Keywords: Peer examiners, OSCE, trained peer examiner, untrained peer examiner.